2012
DOI: 10.1038/mtna.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Inhibitor of Human C-reactive Protein Translation Is Efficacious In Vitro and in C-reactive Protein Transgenic Mice and Humans

Abstract: Observational studies of patients with established rheumatoid arthritis (RA) document a positive correlation between C-reactive protein (CRP) blood concentration and worsening of RA symptoms, but whether this association is causal or not is not known. Using CRP transgenic mice (CRPTg) with collagen-induced arthritis (CIA; a rodent model of RA), we explored causality by testing if CRP lowering via treatment with antisense oligonucleotides (ASOs) targeting human CRP mRNA was efficacious and of clinical benefit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
0
35
1
1
Order By: Relevance
“…To confirm that ASOs that result in adverse events would be identified in this data set, we compared the results obtained with this sample of ASOs to mipomersen, an ASO with clearly defined target-specific adverse effects on the liver. 33,34,35,39 Finally, our phase 1 data showed that advances in the ASO screening process have resulted in an increase in potency and better tolerability with the more recent 2′MOE ASOs in development, 16,17,18,19,41,42 compared with mipomersen.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To confirm that ASOs that result in adverse events would be identified in this data set, we compared the results obtained with this sample of ASOs to mipomersen, an ASO with clearly defined target-specific adverse effects on the liver. 33,34,35,39 Finally, our phase 1 data showed that advances in the ASO screening process have resulted in an increase in potency and better tolerability with the more recent 2′MOE ASOs in development, 16,17,18,19,41,42 compared with mipomersen.…”
Section: Discussionmentioning
confidence: 74%
“…15 However advances in screening, have supported the development of ASOs with minimal injection site reactions and flu-like symptoms observed in clinical trials. 16,17,18,19 These advances include more extensive screening of sites in the target RNA in conjunction with (i) usage of algorithms to filter out sequences and structural motifs, such as CpG, that have been identified as problematic, and sequences that are complementary to nontarget RNAs, and (ii) incorporation of in vitro and in vivo evaluations designed to identify sequences that may produce an exaggerated proinflammatory effect. 20,21,22,23 …”
Section: Introductionmentioning
confidence: 99%
“…For example, in asthma and cancer, CRP-mediated augmentation of Th2 responses would be predicted to promote disease (15, 49). Notwithstanding these caveats, there is growing evidence that CRP is a tonic regulator of the adaptive immune response and this will need to be considered if either purified CRP, or drugs designed to modulate the level of CRP (50, 51), are to be used in patients. In conclusion, CRP can directly affect both innate and adaptive immunity and these capacities are fine-tuned by the protein’s conformation (2, 32, 52, 53), location (54), and concentration (1, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Activated phagocytes produce reactive oxygen species, which are able to alter the immunofluorescent properties of immunoglobulin G (IgG), leading to the further activation of phagocyte fluorescent protein polymers (11,12). The degeneration of IgG inhibits rheumatoid factor, directly resulting in the generation of C-reactive protein (12). This type of reaction manifests itself in the rheumatoid joints in the long term, demonstrating that free radicals exert an important role in the process of chronic inflammation (13).…”
Section: Discussionmentioning
confidence: 99%
“…The reactivity of hypochlorous acid, O 2 -and vitamin C has a great influence on the function of cartilage, resulting in a reduction in the vitamin C content in joint synovial fluid. Activated phagocytes produce reactive oxygen species, which are able to alter the immunofluorescent properties of immunoglobulin G (IgG), leading to the further activation of phagocyte fluorescent protein polymers (11,12). The degeneration of IgG inhibits rheumatoid factor, directly resulting in the generation of C-reactive protein (12).…”
Section: Discussionmentioning
confidence: 99%